Repatriation Taxes and Foreign Cash Holdings: The Impact of Anticipated Tax Reform - De Simone, Lisa; Piotroski, Joseph D; Tomy, Rimmy E (Review of Financial Studies, 2019)
Abstract We examine whether an anticipated reduction in future repatriation taxes affects the amount of cash U.S. multinationals hold overseas. We find that the expected benefits of a repatriation tax reduction are positively associated with accelerated accumulations of global cash holdings once Congress proposed legislation. Additional tests examining domestic and foreign corporations, voluntary disclosures of foreign cash, and corporate payout behavior support our conclusion that observed increases in excess global cash are driven by changes in foreign cash. We also document that U.S. multinationals accumulating excess cash engage in complementary organizational and financial reporting activities designed to maximize expected tax benefits. Received December 7, 2017; editorial decision August 18, 2018 by Editor Andrew Karolyi.